2023
DOI: 10.3390/futuretransp3030057
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Electric Vertical Takeoff and Landing Aircraft into Public Airspace: A Scenario Study

Raj Bridgelall,
Shawn White,
Denver Tolliver

Abstract: The successful deployment of Advanced Air Mobility (AAM) requires the safe integration of electric vertical takeoff and landing (eVTOL) aircraft in non-segregated airspace. However, a lack of practical deployment demonstrations can slow the regulatory progress. This study presents a practical deployment framework for the integration of eVTOL aircraft into public airspace, in accordance with the Federal Aviation Administration (FAA) special airworthiness criteria. This study focused on a corporate use case to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Airspace monitoring for trespassers or unauthorized drone activity constitutes another crucial dimension of heliport security. Drones inform the implementation of safety protocols during high-risk or sensitive operations, thereby augmenting the heliport's overall security framework [54].…”
Section: Security Measuresmentioning
confidence: 99%
“…Airspace monitoring for trespassers or unauthorized drone activity constitutes another crucial dimension of heliport security. Drones inform the implementation of safety protocols during high-risk or sensitive operations, thereby augmenting the heliport's overall security framework [54].…”
Section: Security Measuresmentioning
confidence: 99%
“…These considerations increase uncertainties [24] that exacerbate eVTOL design challenges [25]. Therefore, planners must consider these challenges, and the need for convenient access, airspace sharing, and emergency procedures to provide for vertical take-off and landing services [26]. Moreover, predicting UAM demand is difficult because of uncertainties in factors such as pricing strategy, telecommuting trend, and the lack of Global Positioning System (GPS) trace data [27].…”
Section: Vertiport Locatingmentioning
confidence: 99%
“…These studies indicated that planners should consider demand factors such as population, income, and employment in vertiport placement decision making. However, a survey conducted in Ohio and California by NASA revealed that respondents wanted vertiports to be located close to public transit stations [26]. For predicting the long-term application potential of urban air mobility complementing public transport, Ploetner et al (2020) suggested that UAM resembles a public transport mode in the mobility system and selected a transit mode (train) as the reference mode for UAM in developing an incremental logit model for mode choice [8].…”
Section: Vertiport Locatingmentioning
confidence: 99%